Role of Genetically Engineered System of Male Sterility in Hybrid Production of Vegetables - Ali Anwar, Mohammad Mehdi, (Journal of Phytology, 2009)
Availability of cost effective mechanism/ method to produce large scale hybrid seed utilizing selected parental line is one of the important factors which ultimately determine the commercial viability of hybrid varieties. Manual emasculation increased cost of production, so use of various genetic mechanisms viz; male sterility, self incompatible, gynoccious lines, use of sex regulators and chemical hybridizing agents bases on relative importance in hybrid development in vegetable crops. Among these, genetic emasculation tools male sterility is commonly used for hybrid production. Recombinant DNA techniques have made it possible to engineer entirely new systems of male sterility by disturbing any or a number of developmental steps specifically required for the production of functional pollen within the microspore or for the development of any somatic tissues supporting the microspores. Although engineered male sterility systems are not currently in commercial use, except for possibly the barnase-barstar system, these are likely to have significant importance in future hybrid-breeding programs. The specific mechanisms causing male sterility in vegetables vary from species to species and are subject to influence by environment, and nuclear and cytoplasmic genes. Male sterility may be heritable or transient. It can be induced by anther culture, somatic cell culture, and somatic hybridization. However, the most significant development is the possibility of engineering male sterility by inserting cloned gene sequences which can disrupt any or more than one step during microsporogenesis. The male sterility was, in each case, heritable, associated with normal female fertility, and apparently maternal in its inheritance. Segregation of the transgene did not reverse the male sterile phenotype, producing stable, non transgenic male sterility. The reproducible transgenic induction of mitochondrial rearrangements in plants is unprecedented, providing a means to develop novel cytoplasmic male sterile lines for release as non-GMO or transgenic materials.